Dampak Quarterlife Crisis terhadap Kesehatan Mental pada Dewasa Muda - Sepsita, Vera (TSAQOFAH, 2024)
Quarter Life Crisis is a person entering adulthood who constantly questions the future, is confused when facing problems, and thinks a lot about the past to see whether his current life is in accordance with the life he dreams of. This crisis often occurs in their 20s and often occurs in people who are in the transition period from education to the next career level, which is usually called early adulthood. Research also shows that the Quarter-life Crisis tends to make it difficult to find life goals and things. This has an impact on mental health such as anxiety, depression and decreased psychological well-being. The method used is a literature study by examining relevant journal articles with keywords. The purpose of this article is to determine the impact of the quarter life crisis on the mental health of early adults. Based on the results Research shows that there is a negative impact of the quarter life crisis on mental health in early adulthood.